The advantages of complex anterior abdominal wall plastics with Scarpa’s fascia preservation in patients with class I–II obesity - A. V Kozlov; A. S. Anashkina; P. A. Fedorova; D. A. Kim; T. N. Kozlova (Сибирский научный медицинский журнал, 2023)
Recently, the frequency of treatment of patients with various deformities of the anterior abdominal wall has increased dramatically. Abdominoplasty is a large-scale surgical intervention that entails a number of complications, such as impaired lymphatic drainage, chronic seroma, the formation of “dog ears”, displacement of the navel from the central line. A technology of Scarpa’s fascia preservation (SFP) has been developed to prevent these complications. The aim of this work is to study the effectiveness of treating patients with correction of the tissues of the anterior abdominal wall using SFP technology in comparison with standard abdominoplasty.Material and мethods. The study involved 30 males and females aged 35 to 60 years with class I-II obesity who underwent complex plastic surgery of the anterior abdominal wall. Patients were divided into 2 groups of 15 people: in the 1st group, classical abdominoplasty was performed, in the 2nd, complex plastic surgery of the anterior abdominal wall using SFP technology. Observation of the patients took place in the early and late postoperative periods.Results. Group 2 patients lacked both early postsurgical and chronic seromas, did not develop so-called “dog ears”, which indicates the most favorable course of the postoperative rehabilitation period and the achievement of the best aesthetic results. Also, when using the SFP technology, there were no longterm inflammatory processes, the amount of postoperative exudative fluid in the drains decreased, the pain syndrome was significantly lower, and earlier restoration of the sensitivity of the anterior abdominal wall was noted in comparison with patients who underwent classical abdominoplasty. Complex plastic surgery of the anterior abdominal wall using SFP technology makes it possible to reduce the intensity of pain on the first day by 1.75 times (to 4 ± 1 points, p ≤ 0.05), to speed up the removal of drains (reduce the duration of exudation) by 3 times (to 16 ± 1 h, p ≤ 0.05). According to the BODY-Q scale, in the main group, satisfaction with the aesthetic result was 2 times higher than in the comparison group.Conclusions. Complex anterior abdominal wall plastics with Scarpa’s fascia preservation has a number of significant advantages over classical abdominoplasty.